Dispersive micro-solid phase extraction method using newly prepared poly(methyl methacrylate) grafted agarose combined with ICP-MS for the simultaneous determination of Cd, Ni, Cu and Zn in vegetable and natural water samples. Issue 7 (7th April 2015) - Pourmand, Neda; Sanagi, Mohd Marsin; Naim, Ahmedy Abu; Wan Ibrahim, Wan Aini; Baig, Umair
<x xml:space="preserve">Abstract</x> A new adsorbent (Agarose-g-PMMA) was used in D-μ-SPE for the preconcentration of trace Cd+2, Ni+2, Cu+2 and Zn+2 in aqueous samples prior to ICP-MS detection.